PENGELOLAN DANA DESA DI KECAMATAN KOTA SOE, KABUPATEN TIMOR TENGAH SELATAN, PROVINSI NUSA TENGGARA TIMUR - Dedy Williams Nenobais (Jurnal Ilmiah Wahana Bhakti Praja, 2019)
Abstract This research intend to get a on the management village funds in the sub-district of Soe City. Research objectives to know and to analyze management village funds , factors barrier and supporters management village funds , and strategies overcome factors barrier management village funds in the sub-district of Soe City, district South Central Timor, East Nusa Tenggara Province. The theory that is used is a theory the management of village finance is put forward by nain and because of requirement to build including planning, the implementation of the, effort to manage, reports including the accountability reports. The technique of the collection of data using interviews, documentation and observation. The results of studies show that the management of the village has not completely effective in the sub-district of Soe City, district South Central Timor, East Nusa Tenggara Province that had been determined of the stages the management of village finance is, promised to supply: fine tune the program design, the implementation of the, effort to manage, reports including the accountability reports. Keywords: management, village funds